1974
DOI: 10.1121/1.1903284
|View full text |Cite
|
Sign up to set email alerts
|

Judged acceptability of noise exposure during television viewing

Abstract: Noise masking of television audio signals by flyovers is the most frequently mentioned problem of airport neighbors. This problem was studied in the laboratory using artificial noise. Three studies varied the intensity, duration, and rate (noises per hour) of the noises. Acceptability was found to approximate a logarithmic function of noise energy for changes in intensity, duration, and rate. Thus, the equal-energy principle, which has been generally observed in abstract psychometric experiments, was confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1977
1977
1983
1983

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The data obtained by Langdon, et al [37] for the subjects in Group 1 in the study reported previously and the data of Rice [27,39] at first may appear to be discordant. However, in the Langdon, et al study, in only one instance was the aircraft traffic volume below 15 flyovers per hour.…”
Section: Relationship Between the Number Of Events And Adverse Responsementioning
confidence: 52%
See 4 more Smart Citations
“…The data obtained by Langdon, et al [37] for the subjects in Group 1 in the study reported previously and the data of Rice [27,39] at first may appear to be discordant. However, in the Langdon, et al study, in only one instance was the aircraft traffic volume below 15 flyovers per hour.…”
Section: Relationship Between the Number Of Events And Adverse Responsementioning
confidence: 52%
“…Moreover, both NPL and TNI only account for the range of variations in noise levels with time, but omit other temporal parameters such as the repetition rate of discrete noise events or the rate of change of levels with time -factors that may be important. While no direct evidence from social survey data has shown that these factors have major effects on human response to noise, laboratory studies of the adverse response to multiple events indicate 13 that these factors can affect the adverse human response to noise [27,37,44]. Details of these laboratory studies are given in section 3 of the present report .…”
Section: Reliability Of Noise Exposure Indices In Predicting Communitmentioning
confidence: 89%
See 3 more Smart Citations